Alternativas para a superação de obstáculos relativos à criação de valor, aumento da competitividade e acordos comerciais Internacionais na negociação comercial do Brasil com a China: o caso da soja - Camaret, Luiza de (2005)
China and Brazil have got commercial potentials and strategic partnerships are desired from both sides, but in order to guarantee long term, stable relationship these countries must overcome barriers and obtain mutual gains. The objective of this study was to determine how one can overcome obstacles related to value creation, enhance of competitiveness and international deals in terms of Brazil-China commercial negotiation specifically for soy beans. The CEO of one of the biggest and most important international trading-companies has been contacted and mentioned problems faced by his company in terms of brazillian soy beans sale to chinese clients. Problems such as: the break up of legally based contracts, demanding public pressure, insufficient infra-structure in Brazil for production dispatching, cultural differences, lack of trust, power asymmetry were related and has been analyzed on this study. The perspective used on this study refers to elements, processes and forms of negotiation between these two continental giants.